Age of manager and manager performance a case of selected life insurance unit managers in Iloilo City - Bugante, Jean; Jabagat, Dennis; Pahunao, Grace (2005.)
The study entitled " Age of Manager and managerial Performance : a case of Selected Life Insurance Unit Managers in Iloilo City" is generally one of the cases that thereafter provides meaningful relation to work performance of managers. This study covers thirty (30) unit managers of different life insurance companies in Iloilo City and focuses on how age affects their management performance. It primarily concerned with the manager and customer relations, decision-making and management style. Primary data is made to gather sufficient information and facts. This will be made possible through survey questionnaires. In addition, the researchers also conducted series of library research since it needs various theories and other topics relevant to the study. By these, it was found out that age of managers affect their managerial performance in their respective companies. With the forgoing results, the researchers recommend that the company should prefer middle-aged managers for which age ranges from 36-50 to guarantee an excellent performance, loyalty to the company and effective management style.
Undergraduate Research (Mgt 199-Management Research). -- Iloilo City : University of the Philippines in the Visayas - College of Management, October 2005.